2020
DOI: 10.1093/ajcn/nqaa073
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response effects of dietary protein on muscle protein synthesis during recovery from endurance exercise in young men: a double-blind randomized trial

Abstract: Background Protein ingestion increases skeletal muscle protein synthesis rates during recovery from endurance exercise. Objectives We aimed to determine the effect of graded doses of dietary protein co-ingested with carbohydrate on whole-body protein metabolism, and skeletal muscle myofibrillar (MyoPS) and mitochondrial (MitoPS) protein synthesis rates during recovery from endurance exercise. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
95
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 50 publications
3
95
2
1
Order By: Relevance
“…However, the 4-h time course may be too short to detect the rise in mitochondrial MPS, which is supported by data from Di Donato et al showing a rise in mitochondrial MPS 24-28h following intense endurance exercise, but not 0.5-4.5h post exercise (13). Intriguingly, Churchward-Venne et al brings new life to the debate with their recent study, investigating how different doses of dietary PRO co-ingested with CHO in uence synthesis of myo brillar and mitochondrial MPS (11). In line with previous studies, they report no difference in mitochondrial MPS in response to none or an increasing dose of protein.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…However, the 4-h time course may be too short to detect the rise in mitochondrial MPS, which is supported by data from Di Donato et al showing a rise in mitochondrial MPS 24-28h following intense endurance exercise, but not 0.5-4.5h post exercise (13). Intriguingly, Churchward-Venne et al brings new life to the debate with their recent study, investigating how different doses of dietary PRO co-ingested with CHO in uence synthesis of myo brillar and mitochondrial MPS (11). In line with previous studies, they report no difference in mitochondrial MPS in response to none or an increasing dose of protein.…”
Section: Discussionmentioning
confidence: 88%
“…In line with previous studies, they report no difference in mitochondrial MPS in response to none or an increasing dose of protein. However, by labeling the protein ingested with a L-[1-13 C]-phenylalanine, the research group demonstrated that incorporation of dietary protein-derived L-[1-13 C]-phenylalanine into de novo synthesis of mitochondrial protein increased dosedependently after ingestion of 15, 30 and 45 g of PRO at 360 min post exercise (11). In support of a positive interaction between consuming protein post exercise and mitochondrial adaptations, Hill et al demonstrated that a 2-week dietary intervention of co-ingestion with CHO-PRO compared to CHO, resulted in signi cantly greater increases in PGC-1α 6h after endurance exercise (14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations